Rising strong as a spiritual practice eaudiobook - Brown, Brené (Sounds True, 2017)
Spirituality—How It Makes Us Stronger   With her previous bestsellers, Dr. Brené Brown helped us realize that vulnerability is the birthplace for trust, courage, joy, creativity, and love. Yet a willingness to be vulnerable means accepting that life will sometimes knock us down. Where do we find the strength to get back up? In her research on resilient people , Brené discovered a key factor. “Without exception,” she says, “the concept of spirituality emerged from the data as a critical component of resilience and overcoming struggle.” On Rising Strong as a Spiritual Practice, Brené offers an in-depth exploration of this key aspect of wholehearted living, including:   • The spiritual dimension of the Rising Strong process: the Reckoning, the Rumble, and the Revolution • A sense of belonging—how spirituality encourages us to be ourselves instead of trying to change in order to fit in • Why the sense of perspective provided by a spiritual practice helps us find meaning and purpose • “Are we doing the best we can?”—How faith in humanity can help us become more compassionate and less judgmental • Why the spiritual understanding of death and rebirth are invaluable in the process of forgiveness   On Rising Strong as a Spiritual Practice, Brené defines spirituality as something not reliant on religion, theology, or dogma—rather, it is a belief in our interconnectedness and in a loving force greater than ourselves. Whether you access the sacred through traditional worship, solitary meditation, communion with nature, or creative pursuits, one thing is clear: cultivating your own approach to spirituality gives you an irreplaceable resource to help you persevere through hard times and arise stronger and wiser than before.